Contrasting GC-content dynamics across 33 mammalian genomes: Relationship with life-history traits and chromosome sizes - Romiguier, Jonathan; Ranwez, Vincent; Douzery, Emmanuel J.P.; Galtier, Nicolas (Genome Research, 2010)
The origin, evolution, and functional relevance of genomic variations in GC content are a long-debated topic, especially in mammals. Most of the existing literature, however, has focused on a small number of model species and/or limited sequence data sets. We analyzed more than 1000 orthologous genes in 33 fully sequenced mammalian genomes, reconstructed their ancestral isochore organization in the maximum likelihood framework, and explored the evolution of third-codon position GC content in representatives of 16 orders and 27 families. We showed that the previously reported erosion of GC-rich isochores is not a general trend. Several species (e.g., shrew, microbat, tenrec, rabbit) have independently undergone a marked increase in GC content, with a widening gap between the GC-poorest and GC-richest classes of genes. The intensively studied apes and (especially) murids do not reflect the general placental pattern. We correlated GC-content evolution with species life-history traits and cytology. Significant effects of body mass and genome size were detected, with each being consistent with the GC-biased gene conversion model.
10.1101/gr.104372.109